Magnetic Resonance Image Findings in A Rare Case of Bilateral Knee Pain in A Small Patella Syndrome Patient - Bin Didi Indra, Faris Indra Prahasta; Chen, Loo Wen; Bin Ibrahim, Mohd Anuar Ramdhan; Han, Ong Lik (Bangladesh Journal of Medical Science, 2023)
Congenital aplasia or hypoplasia of the patella can manifest as an isolated disease or more commonly part of rare genetic disorders such as small patella syndrome (SPS). To our knowledge this is the first report of a patient with small patella syndrome who complained of bilateral knee pain with no preceding injury. Magnetic resonance imaging (MRI) revealed early degenerative changes of the knee joints which had not been mentioned in any literature. The MRI findings in our case are important as it would help in finding the cause of the pain and allow early treatment to be initiated thus delaying the progression of the arthritic changes. Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 926-931